IMPLEMENTASI METODE PEMBELAJARAN EXPERIENTIAL LEARNING UNTUK MENINGKATKAN AKADEMIK SANTRI SMA PONDOK PESANTREN - Djone Georges Nicolas; Timothy Amien Rk.; Soneta Sang Surya Siahaan; Iwan Ramadhan; Lilik Huriyah (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
The experiential learning method is a model of teaching and learning process that can make students build their knowledge and skills with experiences gained directly. The experiential learning method can provide opportunities for students to decide on experiences that can be one of the focuses in developing skills and also improving the talents they have. This study aims to find out about experiential learning methods carried out in social life to improve the academics of female students at the Islamic Boarding School. The research method used is the descriptive analysis method by approaching the qualitative side. The research subjects in this research process are students at the Islamic Boarding School. Data were collected by conducting participant observation of the learning method in the classroom and also the activities of students around the boarding school. Interviews, questionnaires, and documentation were also conducted as a way to support the data needed in the research process. The results of this study present that the experiential learning method in the social and academic life of students in Islamic Boarding Schools related to the learning process and student activities is carried out quite well with various kinds of efforts made by the Islamic Boarding Schools. However, there are still some activities that require attention and attention.